Pediatrik başlangıçlı multipl sklerozlu hastalarda desteksiz üst ekstremite egzersiz testinin yorgunluk ve endurans ile ilişkisinin araştırılması - Doğan Boy, Nergiz (My University, 2024)
Amaç: Pediatrik Başlangıçlı Multiple Sklerozlu (PBMS) hastalarda UULEX’in yorgunluk ve endurans ile ilişkisinin araştırılmasıdır. Gereç ve yöntem: Bu çalışmaya çocukluk çağında MS tanısı almış 13-21 yaş aralığında 15 hasta ve 15 sağlıklı kontrol grubu dahil edildi. Katılımcılara UULEX, 6 dk yürüme testi (6DYT), Pinch metre ve Jamar ile kavrama kuvveti ölçümü yapıldı. Ayrıca MYEÖ ve PEDsQL değerlendirmesi yapıldı. Test-tekrar test güvenirliğini belirlemek amacıyla UULEX, 6DYT ve kavrama kuvvet ölçümleri ilk iki değerlendirme bir saat arayla, üçüncü değerlendirme ise bir hafta sonra olacak şekilde toplamda üç kez uygulandı. Elde edilen veriler ile UULEX’in yorgunluk ve endurans ile ilişkisine bakıldı. Bulgular: Çalışma grubu yaş ortalaması 16,7 yıl olan 9 kadın 6 erkek, kontrol grubu yaş ortalaması 16,9 yıl olan 7 kadın 8 erkek katılımcıdan oluşmaktadır. Çalışma grubu kontrol grubuna göre düşük UULEX, 6DYT, pinch, lateral ve maksimal kavrama kuvvetine sahiptir. Çalışma grubunun kontrol grubuna göre PEDsQL puanları düşük, MYEÖ puanları yüksek bulunmuştur. UULEX çalışma grubunda 6DYT ve el kavrama kuvveti ile, kontrol grubunda ise pinch ve lateral kavrama kuvveti ile istatistiksel olarak anlamlı bulunmuştur (p=<0,05). UULEX tüm parametrelerinde sınıf içi güvenirliliği yüksek bulunmuştur (p=<0,001). Sonuç: PBMS’li bireylerin erişkinlik döneminde engellilik düzeylerinde artış meydana gelmektedir. Fonksiyonel yeteneklerinin kaybını geciktirmek ve günlük yaşamda bağımsızlıklarını devam ettirmek için düzenli ve kapsamlı değerlendirmeler yapılmalıdır.

Objective: To investigate the relationship of UULEX with fatigue and endurance in patients with Pediatric Onset Multiple Sclerosis (PBMS). Material and Methods: Fifteen patients between the ages of 13-21 who were diagnosed with MS in childhood and 15 healthy control groups were included in this study. Grip strength measurements were performed on the participants using UULEX, 6 minute walk test (6MWT), Pinch meter and Jamar. Additionally, the MYEÖ and the PEDsQL were evaluated. In order to determine the testretest reliability, UULEX, 6MWT and grip strength measurements were applied three times in total, with the first two assessments taking place one hour apart and the third assessment one week later. With the data obtained, the relationship between UULEX and fatigue and endurance was examined. Results: The study group consists of 9 female and 6 male participants with an average age of 16.7 years, and the control group consists of 7 female and 8 male participants with an average age of 16.9 years. The study group had lower UULEX, 6MWT, pinch, lateral and maximal grip strength compared to the control group. PEDsQL scores of the study group were found to be lower and MYEÖ scores were higher than the control group. UULEX was found to be statistically significant with 6MWT and hand grip strength in the study group, and with pinch and lateral grip strength in the control group (p=<0.05). UULEX was found to have high intra-class reliability in all parameters (p=<0.001). Conclusion: Disability levels increase during adulthood with PBMS. Regular and comprehensive evaluations should be made to delay the loss of functional malfunction and maintain its range in daily life.
Investigation of the relationship between unsupported upper-limb exercise test and fatigue and endurance in patients with pediatric-onset multiple sclerosis
Keywords: endurance; endurans; fatigue; Multipl skleroz; Multiple sclerosis; pediatric onset multiple sclerosis; pediatrik başlangıçlı multiple skleroz; UULEX; yorgunluk